Toxicity of protease-resistant domains from the delta-endotoxin of Bacillus thuringiensis subsp. israelensis in Culex quinquefasciatus and Aedes aegypti bioassays. - Pfannenstiel, M A (1990)
The mosquitocidal glycoprotein endotoxin of Bacillus thuringiensis subsp. israelensis was digested with chymotrypsin to yield protease-resistant domains which were then separated from smaller protease digestion products by high-performance liquid chromatography. Once purified, the domains no longer bound wheat germ agglutinin, a lectin which binds N-acetylglucosamine (GlcNAc) and GlcNAc oligomers. Purified protease-resistant domains were as toxic for Culex quinquefasciatus larvae as intact solubilized toxin. In separate experiments, the toxicity of chymotrypsin-digested endotoxin for Aedes aegypti larvae was reduced fivefold or more. A model is presented in which GlcNAc-containing oligosaccharides are required for toxicity for A. aegypti larvae but not C. quinquefasciatus larvae.